Que perspectivas para África em 2025 - Almeida, E. C. (Novo Jornal, 2025)
A text where I analyze how the year 2025 could be for Africa to face a complex and dynamic scenario, full of opportunities and challenges, as it will have to interact, even more energetically, with the BRICS and African Growth and Opportunity. Act (AGOA), given that it will have to adapt to the possible new and still unknown policy of the United States (US), under the leadership of Donald Trump, towards the Continent.